PEMBENTUKAN KARAKTER DISIPLIN SISWA MELALUI IMPLEMENTASI BEHAVIORISME DALAM PEMBELAJARAN PAI DI SEKOLAH DASAR - Rohmaniyah Rohmaniyah; Abd. Hadi Rohmani (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
This study aims to describe the implementation of behaviorism in Islamic religious education learning as the formation of students’ disciplined character and its challenges. The research method is descriptive qualitative. Interviews, observations and documentation are used as data collection techniques. Furthermore, the data analysis stage consists of reduction, presentation and drawing conclusions. The implementation of behaviorism conducted with three approaches, including the habituation method, reward giving, and punishment. The habituation aspect is conducted by coming to school on time, implementing congregation Dhuha and Dzuhur prayers, discipline in cleaning the classroom, begining and finish learning with prayer. The reward aspect given to students is manifested in the form of verbal, visual praise or other special concrete gifts. The punishment aspect is carried out by means of reprimands, reduction of student rights such as recess time, and physiological-constructive such as cleaning the school yard. The forms of challenges that occur such as the characteristics of students who come from different backgrounds, the influence of the social environment, culture, and peer interactions.